NGHIÊN CỨU CHẾ TẠO MÀNG LỌC NANO VÀ KHẢO SÁT MỘT SỐ YẾU TỐ ẢNH HƯỞNG ĐẾN TÍNH CHẤT TÁCH CỦA MÀNG - Dung, Trần Thị; Hà, Phạm Thị Thu; Thương, Vũ Quỳnh (Vietnam Journal of Science and Technology, 2012)
PREPARATION OF NANOFILTRATION MEMBRANE AND INFLUENCE OF SOME CONDITIONS ON MEMBRANE SEPARATION PROPERTY Nanofiltration membrane has been fabricated using an immersing phase inversion method. Influence of some preparation conditions and operation parameters on membrane separation performance has been investigated in terms of the membrane retention for sodium chloride and/or heavy metal ions in a dilute feed solution. The obtained experimental results showed that the composition of polymer in a casting solution and the solvent evaporation time highly influence on separation property of the formed nanofiltration membranes. Also, an applied pressure as well as concentration of ions in a feed solution are important factors that determine separation capacity of membranes.